Comparative Study of Microorganisms in Diabetic and non-diabetic Patients with Moderate and Severe Periodontitis - Grace Alejandra Cabezas Cantos; Jonathan Armando Yanza Freire; Ingrid Polethe Morillo Gavilema; Aisha Adamarys Pineda Gómez (Revista Finlay)
Foundation: periodontal disease is a common oral condition, characterized by inflammation and progressive destruction of the supporting tissues around the teeth. Periodontal disease has been associated with factors related to hygiene, cigarette smoking and systemic diseases such as diabetes. Objective: to describe the relationship that exists between the microorganisms found in diabetic and non-diabetic patients who presented periodontitis in moderate and advanced stages at the Hospital of the Ecuadorian Institute of Social Security and the González Suárez Health Center in the period June-August of the 2023. Methods: a descriptive and cross-sectional study was carried out at the Hospital of the Ecuadorian Social Security Institute and at the González Suárez Health Center in the period June-August 2023. The sample consisted of 23 patients who met the criteria of inclusion and exclusion. The variables were analyzed: age, sex and isolated germs. Within the statistical analysis, absolute and relative frequencies were used as summary measures. Results: diabetic patients over 50 years of age prevailed (N=10; 43.4 %), with Odds Ratio of 2.61. Streptococcus viridans was present in 100 % of the sample studied, but it did not have a statistically significant relationship. Candida albicans had a prevalence of 73.1 % in diabetic patients with an OR of 1.6. Conclusions: the results revealed significant differences in the microbial composition between the groups of patients with moderate and severe periodontitis.